2010
DOI: 10.1071/ch10297
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of an Allene Bearing Two Dimethoxythioxanthene Groups by Oxidation via a Vinyl Cation Intermediate

Abstract: With the objective of preparing an isolable triplet carbene, we have carried out the oxidation of an allenic compound bearing two thioxanthene moieties (5). Relatively weak oxidants such as Ph3C+BF4 – gave 8, which is the conjugate acid of 5, as a result of a one-electron oxidation followed by hydrogen abstraction, whereas relatively strong oxidants such as SbCl5 furnished a dicationic ketal (9) as a consequence of oxidation and demethylation. Computations on the supposed dicationic intermediate suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Oxidation waves were observed at E pa = 1.23 and 1.53 V (in 100 mM TBAPF 6 /CH 2 Cl 2 , Glass Carbon (GC), versus Saturated Calomel Electrode (SCE), room temperature) for 7a and E pa = 0.74 and 1.08 V (in 100 mM TBAPF 6 /CH 2 Cl 2 , GC, versus SCE, room temperature) for 7b . These results suggested that oxidation processes would proceed in two steps like the allenic compound previously examined by us . Also implied was that 7a might not be suitable as a precursor because its high second oxidation potential would be troublesome for mild oxidation and the product carbene was expected to be unstable.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Oxidation waves were observed at E pa = 1.23 and 1.53 V (in 100 mM TBAPF 6 /CH 2 Cl 2 , Glass Carbon (GC), versus Saturated Calomel Electrode (SCE), room temperature) for 7a and E pa = 0.74 and 1.08 V (in 100 mM TBAPF 6 /CH 2 Cl 2 , GC, versus SCE, room temperature) for 7b . These results suggested that oxidation processes would proceed in two steps like the allenic compound previously examined by us . Also implied was that 7a might not be suitable as a precursor because its high second oxidation potential would be troublesome for mild oxidation and the product carbene was expected to be unstable.…”
Section: Resultsmentioning
confidence: 79%
“…Thus, we envisaged that this feature would also be favorable for the introduction of other rigid steric protecting groups around the anticipated carbenic center. To this end, we examined the oxidation reaction of allenic precursor 5 . Unfortunately, this resulted in the generation of dicationic ketal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Our method was based on the two-electron oxidation of allenic precursors bearing two thioxanthene or acridene moieties. [7][8][9] Thus, we attempted the oxidation of allenic compound 3 bearing two dimethoxythioxanthene moieties [10] that was previously reported by our group (Scheme 2). However, the oxidation of 3 did not furnish a stable triplet carbenic species but instead provided ketal 4, likely via a singlet ground-state carbene.…”
Section: Introductionmentioning
confidence: 95%
“…However, the oxidation of 3 did not furnish a stable triplet carbenic species but instead provided ketal 4, likely via a singlet ground-state carbene. [7] According to theoretical calculations, this decomposition resulted from the vinyl cation character of the generated dicationic species.…”
Section: Introductionmentioning
confidence: 99%
“…J. Chem. captures the flavour of the meeting by publishing 15 papers covering gold catalysis in organic synthesis, [2] corannulene-based curved p-radicals, [3] formation of 1,3-diradicals from bicyclic azo compunds, [4] electron spin resonance spectroscopy of a,n-didehydrotoluene diradicals, [5] allene-carbene conversion in the thioxanthene series, [6] nitrene and free radical intermediates from azidomethylacetophenones, [7] s-hole binding, [8] synthesis and reactions of cyclobutenimines, [9] development of methodology for natural product synthesis, [10] organic-inorganic composite nanoscale materials, [11] matrix isolation of nitrile sulfides, [12] unusual thioketenes and extended cumulenes, [13] mixed cyclophanes, [14] photoelectron spectroscopy of short-lived molecules containing Ge and As, [15] and the HERON reaction (Heteroatom rearrangements on nitrogen) of N-acyloxy-N-alkoxyamides. [16] We are pleased to acknowledge Dr Brett Schwartz for designing the cover art.…”
mentioning
confidence: 99%